After you - Moyes, Jojo (Penguin Books, 2016)
Lou Clark has lots of questions. Like how it is she's ended up working in an airport bar, spending every shift watching other people jet off to new places. Or why the flat she's owned for a year still doesn't feel like home. Whether her close-knit family can forgive her for what she did eighteen months ago. And will she ever get over the love of her life. What Lou does know for certain is that something has to change. Then, one night, it does. But does the stranger on her doorstep hold the answers Lou is searching for - or just more questions? Close the door and life continues: simple, ordered, safe. Open it and she risks everything. But Lou once made a promise to live. And if she's going to keep it, she has to invite them in . . .